STRENGTHENING THE PEDAGOGICAL COMPETENCE OF TECHERS AT TAMAN PENDIDIKAN AL-QUR’AN (TPQ) (QUR’ANIC EDUCATIONAL PROGRAM) THROUGH A SUSTAINABLE DEVELOPMENT PROGRAMS IN SOUTHERN PURWOKERTO REGION - Sutrimo Purnomo; Novi Mulyani; Munjin; Muh. Hanif; Windhariyati Dyah Kusumawanti; Khafifatul Fian; Umi Khomsiyatun (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study aims to analyze the pedagogical competence of teachers at Taman Pendidikan Al-Qur’an (TPQ) or the Qur'anic Educational Program in the Southern Purwokerto Region using a Community-Based Research (CBR) approach through four stages: foundation laying, planning, data collection and analysis, and action through Focus Group Discussions (FGD). The initial stage revealed that only 28% of TPQ teachers demonstrated sufficient competence in learning management, while 52% were categorized as suboptimal. Regarding the use of strategies and teaching methods, only 39.6% of teachers exhibited adequate competence, whereas 48.4% lacked these skills. The second stage involved implementing a pedagogical competence enhancement program, which included planning, training in learning management, strengthening teaching strategies and methods, and providing mentoring during implementation. Subsequent evaluation through FGDs demonstrated a significant improvement in the pedagogical competence of TPQ teachers. Competence in learning management increased to 61.2%, while competence in utilizing teaching strategies and methods rose to 72.2%.